2021
DOI: 10.3390/plants10112413
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Content of Astaxanthin and Its Esters from Microalgae Haematococcus pluvialis by HPLC-DAD and LC-QTOF-MS after Extraction with Various Solvents

Abstract: Haematococcus pluvialis, a unicellular green microalga that produces a secondary metabolite under stress conditions, bears one of the most potent antioxidants, namely xanthophyll astaxanthin. The aim of our study was to determine the content of astaxanthin and its esterified forms using three different solvents—methyl tert-butyl ether (MTBE), hexane isopropanol (HEX -IPA) and acetone (ACE)—and to identify them by using high performance liquid chromatography coupled with diode array detection and the quadrupole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A comprehensive utilization of microalgae could significantly reduce the cost of microalgae biofuels, which included microalgae cultivation using wastewaters in outdoor raceway ponds (Arora et al, 2016;Gao et al, 2018;Keerthana et al, 2020) and the production of bioactive substances such as polysaccharides (Li et al, 2019), antiviral substances (Fritzsche et al, 2021), bioactive peptides (Donadio et al, 2021), and carotenoids (du Preez et al, 2021;Todorovićet al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive utilization of microalgae could significantly reduce the cost of microalgae biofuels, which included microalgae cultivation using wastewaters in outdoor raceway ponds (Arora et al, 2016;Gao et al, 2018;Keerthana et al, 2020) and the production of bioactive substances such as polysaccharides (Li et al, 2019), antiviral substances (Fritzsche et al, 2021), bioactive peptides (Donadio et al, 2021), and carotenoids (du Preez et al, 2021;Todorovićet al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the future, it would be useful to test several different solvents for the extraction of phenolic compounds from Berula erecta in order to determine the most effective one. In different plant species, the choice of extraction solvent has been shown to influence the amount of bioactive compounds extracted [ 65 , 66 , 67 ]. New trends in chemistry and in environmental legislation have placed demands on the use of so-called “green” extraction processes, so, in the future, it would also be suitable to test the efficiency of extraction with deep eutectic solvents [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different delivery systems can effectively improve the digestion rate and bioavailability of AST-Es. 44 Yang et al 32 experimentally showed that the bioavailability of AST-E with different molecular structures changed within 24 h, and compared with AST-F and AST-ME, AST-DE had a higher bioavailability at all periods. The bioavailability of AST-Es increases under certain conditions; AST-E bioavailability can be increased by increasing the amount of unsaturated fatty acids.…”
Section: Improved Ast Bioavailabilitymentioning
confidence: 99%
“…The maximum absorption peak of AST liposomes and microemulsions in mouse serum was at 7 h, which was the shortest time compared with the other systems. Different delivery systems can effectively improve the digestion rate and bioavailability of AST-Es . Yang et al experimentally showed that the bioavailability of AST-E with different molecular structures changed within 24 h, and compared with AST-F and AST-ME, AST-DE had a higher bioavailability at all periods.…”
Section: Biomedical Activitiesmentioning
confidence: 99%